Effectiveness of implementing waste bank operation on solid waste minimization in Kundasang, Sabah, Malaysia - Alias, Fatma Sabariah (2018)
Modernization and urbanization has changing the ways how Malaysian live, think and act. With the rapid changing culture, Malaysians produce more waste than before. Nowadays, 38,000 tonnes of waste was produce per day in Malaysia which reached 12.8 million tonnes of waste generated per year. These striking figure has become a major problem to the country due to the latest figure has exceeded the government’s projected waste production in year 2020 which is 30,000 tonnes per day. Therefore, the government attempts to increase the national recycling rates from the current 17.5% to at least 22% by year 2020. However, the contributions of household were crucial in minimizing solid waste generation effectively by recycling practices. Thus, this study investigated the effectiveness of solid waste minimization through the implementation of waste bank operation in Kundasang, Sabah. Waste bank were operated to engage and empowering the communities in recycling practices and creating a sense of citizen role in environmental awareness. Hence, a pre and post survey was conducted before and after the implementation of waste bank operation. Results from the pre survey, revealed about 41% of respondents dispose their waste by burning due to none solid waste collection services by local authority which resulting the respondents dispose their waste improperly, thus contributing to the solid waste problem in Kundasang. Subsequently, about 65.7% of respondents didn’t separate their waste because of no time (35.7%), no recycling facilities (21.7%), do not know how to separate (4.7%) and feel laziness (3.7%) in practicing solid waste separation at household. Additionally, due to higher tourism activities at Kundasang have worsened the scenario. As recycling practices effective in minimizing the solid waste generation, thus waste bank operation were proposed to be implemented at Kundasang town. However, about 61% of respondents willing to participate in the waste bank operation where almost all range age from 19 years below until 60 years old were interested. Besides that, the pre survey revealed about 63% of respondents was willing to participate in the waste bank because of incentives provided. Nonetheless, incentives were provided as the supporting factor to motivate the community participate in the waste bank operation. Thus, during the 6 months of waste bank operation, there are about 53 participants were registered as the waste bank member where the members brings their recyclables waste to be sort, weight and recorded. About 2501.30 kg recyclables waste were collected in two-phase which are in phase 1 operated in July until October 2016 and phase 2 from January until March 2017. The highest recyclables waste collection were dominance by 1114.50 kg of paper, then followed with 672.20 kg of box/cardboard, 258.30 kg of plastic, 102.45 kg of aluminum cans, 231.40 kg of metal and 122.45 kg of glass with total waste bank revenue has achieved RM 599.44. The waste bank has been successfully operated as the results from the post survey shows the positive changes in respondent’s awareness as an increasing in solid waste separation (47.3% respondents). Moreover, positive changes in respondent’s attitude occurred in the reduction of 18% from the pre-survey results in solid waste disposal which only 23% of respondents dispose their waste improperly. On the other hand, although 66% of the respondents know the waste bank operation, but only 17.7% were took action by participate in the waste bank. The main reason were due to do not get any information (16.3 %), less publicity (12.7%), location of the waste bank (4.7%), and others (0.3%) do not collect recyclables which had influenced the number of participation in the waste bank. Although the recycling rate for the respondents was still low as 0.26 kg/person/day but the implementation of waste bank has create a positive impacts to the Kundasang community which enhancing the potential of waste bank as the accessible and convenience recyclables collection at the community level and the opportunity in generating additional income. Furthermore, the implementation of waste bank operation has revealed its effectiveness as the net benefits were highly positive as calculated RM 14,583.28 which overweighs the costs of waste bank operation. The benefits and costs also indicate that the waste bank operation was a feasibility project where the collection effectiveness reached 17.7% with potential diversion rate was 17.7%. In the nutshell, the implementation of the waste bank operation brought benefits to the community by empower and engage the local community into the planning and management of solid waste minimization especially in recycling practices within their own neighborhood where the intention was to encourage and increase the awareness among the community especially in the rural and small communities.